Enhancing Consumer Trust in Organic Products through The Role of Certification, Transparency, and Digital Innovation in Emerging Markets: A Literature Review - SAMIR LABIAD; SAIDA MARSO (Communications of International Proceedings, 2025)
Consumer trust remains a critical factor in the growth of the organic food market, especially in the emerging markets where cynicism still prevails regarding products’ certification, authenticity, and traceability. This study, focussing on Morocco, explores how product certification, supply-chain transparency, and digital innovation can be used to enhance consumer trust in organic foods in the emerging markets. Despite the growing consumption of organic foods globally, the existing literature majorly focus on developed economies, with very limited exploration of the unique challenges of the emerging markets which often suffer from underdeveloped regulatory frameworks and disjointed distribution networks. The study attempts to address this gap through a systematic literature review of publications between 2008 and 2025 of peer-reviewed journal articles. Seventy articles focussing on the trust issues in emerging markets were reviewed, where twenty-five were selected given their relevance to certification, transparency, and application of digital technology to influence organic food consumption. The study finds that robust certification mechanisms, clear organic labelling, and trusted regulatory bodies and frameworks do enhance consumer trust. Moreover, the application of blockchain technologies, product traceability apps and QR codes help reduce information asymmetry among consumers. Interestingly, Moroccan consumers demonstrated their preference for in-season locally-produced, easily accessible, and clearly-labelled food products. The study recommends integrated stakeholder approaches, including policy-makers, producers and technology providers, to building consumer trust in organic products and the organic sector in emerging markets. The findings contribute to advancing literature and practical mechanisms for endorsing sustainable consumer behaviour in the global organic food market.
Keywords: organic products; consumer trust; certification; transparency; digital innovation; emerging markets